New cationic chlorin as potential agent for antimicrobial photodynamic therapy - N. V. Suvorov; V. V. Shchelkova; E. V. Rysanova; Z. T. Bagatelia; D. A. Diachenko; A. P. Afaniutin; Yu. L. Vasil’ev; E. Yu. Diachkova; I. C. Santana Santos; M. A. Grin (Biomedical Photonics)
Multiple drug resistance is a major global health security risk. Increasing resistance of bacteria to existing drugs puts on the agenda the search for alternative ways to combat antibiotic-resistant pathogens. One of these innovative methods is antimicrobial photodynamic therapy (APDT), which is equally eﬀective against antibiotic-sensitive and antibiotic-resistant pathogens. The most eﬀective photosensitizers (PS) for APDT are molecules containing positively charged groups in their composition. In this work, we have obtained a new cationic derivative of natural chlorin containing a pyridazine group in its composition, the introduction of which occurs using click chemistry approaches. The antimicrobial photoinduced cytotoxicity of the proposed cationic PS, as well as its uncharged precursor, was assessed against a number of gram-positive and gram-negative bacteria: S. aureus, K. pneumoniae, E. faecalis, P. aeruginosa. It has been shown that cationic chlorin exhibits an increased bactericidal eﬀect when irradiated with light (λ = 660 nm, Ps = 70.73 mW/cm2) compared to its base form. When microbial suspensions were incubated with 24 μM cationic PS and subsequently irradiated, a signiﬁcant bactericidal eﬀect was observed against all of the aforementioned bacteria. As a result of microbiological studies, it was demonstrated that the proposed cationic PS exhibits high photoinduced antimicrobial activity.